Seeding and branching out: sixty years of a laboratory for plants in archaeology. - Fuller, Dorian Q; Colledge, Sue; Orellana, Ayelen Delgado (Archaeology International, 2025)
Current refurbishment of the archaeobotany laboratory and integration of its extensive reference collections are underway. In addition to archaeobotanical remains, there are more than 20,000 accessions of modern reference specimens, mainly seeds, fruits and wood. The history of how these collections have grown is summarised, starting with the first phase when Geoffrey Dimbleby was Professor of Human Environment (1964–79), and during which Cecilia Western built up reference collections of wood. A second phase dates from the 1980s and 1990s with Professor David Harris and Archaeobotany Lecturer Gordon Hillman, who undertook research, fieldwork and teaching, especially in relation to agricultural origins and Near Eastern seeds. Jon Hather's research complemented this with his work on tubers, woods and tropical nuts. The third phase, since 2000, has seen accessions added from broader geographical origins and including wood and seeds, as well as phytoliths, 'plant fibre samples' and historic British cereal samples.